Need for empirical evidence to support use of social license in conservation: reply to Garnett et al. - Dave Kendal; Rebecca M. Ford (Conservation Biology, 2018)
Article impact statement : Understanding the role of social license informs managers and policy makers of community support and acceptance of conservation actions.